Tipografia popular: potências do ilegível na experiência do cotidiano - Bruno Guimaraes Martins (2005)
Besides traditional medias, popular typography is a discrete communicative act in everyday life space. These anonymous writing of ordinary people is capable to estimulate a criative activity on the reader of their eccentric and irregular characters. When the principles of legibility are not present, type emerge as an enpowerment of meaning, becaming far from the idea of a transparent sign. This unusual reading process made possible by formal and contextual singularities of popular typography is the main object of this dissertation. Since ten images of popular typography, chosen by their eccentricity from the rules of lebilility in classic typography, is made an investigation of how, during reading process, the reader attention is guided simultaneously for the materialities of these texts and for the complexity of everyday life space.